COMPARATIVE ANALYSIS OF ANTERIOR KNEE PAIN IN TRANSPATELLAR AND MEDIAL PARAPATELLAR TENDON APPROACHES IN TIBIAL INTERLOCKING NAILING - Ahmad, Saeed; Ahmed, Ashfaq; Khan, Latif; Javed, Shahzad; Ahmed, Naeem; Aziz, Amer (Journal of Ayub Medical College Abbottabad, 2016)
Background: Anterior knee pain is the most common complaint after intramedullary nail of the tibia.The incidence of anterior knee pain ranges from 10-86% and the exact ethology is unclear. Transpatellar tendon approach is commonly used for tibial intramedullary interlocking nailing but it can also be done through medial parapatellar tendon approach. The objective of the study was to compare post-operative anterior knee pain after intramedullary nailing technique by transpatellar approach compared to medial parapatellar approach. Methods: This randomized controlled trial was carried out in Department of Orthopaedic and Spine Surgery, Ghurki trust teaching hospital, Lahore from 20th February to 19th Nov 2015. Sixty patients who presented at emergency department for the treatment of simple tibial shaft fractures were included in the study. They were divided into two groups with 30 patients in each group, Group A containing patients operated through transpatellar tendon approach while group B containing patients operated through medial parapatellar tendon approach. Results: In Group A, 27 patients were male and 3 patients were female with a mean age of 28.667±9.63 while in Group B, 28 were male and 2 were female with a mean age of 34.63±15.82. The main cause of tibial shaft fractures were RTA followed by fall. In Group A mean anterior knee pain was 4.4 while in Group B, it was was 2.5 with a p value of .000. Conclusion: This study shows that medial parapatellar tendon approach causes less pain as compared to transpatellar approach. Keywords: Tibial shaft fractures; Transpatellar Approach; Medial parapatellar Approach; Intra-medullary nailing